Phase variation of a Type IIG restriction-modification enzyme alters site-specific methylation patterns and gene expression in Campylobacter jejuni strain NCTC11168 - Anjum, Awais; Kelly, Brathwaite; Aidley, Jack B; Connerton, Phillippa L.; Cummings, Nicola J; Parkhill, Julian; Connerton, Ian F.; Bayliss, Christopher D (Oxford University Press, 2016)
Phase-variable restriction-modification systems are a feature of a diverse range of bacterial species. Stochastic, reversible switches in expression of the methyltransferase produces variation in methylation of specific sequences. Phase-variable methylation by both Type I and Type III methyltransferases is associated with altered gene expression and phenotypic variation. One phase-variable gene of Campylobacter jejuni encodes a homologue of an unusual Type IIG restriction-modification system in which the endonuclease and methyltransferase are encoded by a single gene. Using both inhibition of restriction and PacBio-derived methylome analyses of mutants and phase-variants, the cj0031c allele in C. jejuni strain NCTC11168 was demonstrated to specifically methylate adenine in 5′CCCGA and 5′CCTGA sequences. Alterations in the levels of specific transcripts were detected using RNA-Seq in phase-variants and mutants of cj0031c but these changes did not correlate with observed differences in phenotypic behaviour. Alterations in restriction of phage growth were also associated with phase variation (PV) of cj0031c and correlated with presence of sites in the genomes of these phages. We conclude that PV of a Type IIG restriction-modification system causes changes in site-specific methylation patterns and gene expression patterns that may indirectly change adaptive traits.